1981
DOI: 10.1111/j.1365-2818.1981.tb01284.x
|View full text |Cite
|
Sign up to set email alerts
|

In situ liquid propane jet‐freezing and freeze‐etching of monolayer cell cultures

Abstract: SUMMARY A procedure for in situ liquid propane jet‐freezing of unfixed and unglycerinated monolayer cell cultures is described. We have used the method to study monolayer cultures of rat Sertoli cells and human monocytes. The described procedure gives a cooling rate during specimen freezing high enough to yield adequately frozen specimens even in the absence of any cryo‐protectant. Use of the procedure therefore eliminates artefacts usually caused by cell fixation and addition of cryoprotectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1982
1982
1988
1988

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Propane jet freezing, introduced in the midseventies (Moor et al, 1976;Muller et al, 19801, is the inverse of spray freezing: Liquid propane cooled to near liquid nitrogen temperature is sprayed onto the sample at high velocity. Several investigators, ourselves included, have built their own version of the device (Burstein and Maurice, 1979;Linder and Staehelin, 1978;Espevik and Elgsaeter, 1981;Pscheid et al, 1981;Knoll et al, 19821, and commercial models are available from RMC, Inc., Tucson, AZ (based upon our design), and Balzers Corporation, Nashua, NH. In general, the protocol is as follows (see Figs.…”
Section: Propane Jet Freezingmentioning
confidence: 99%
See 2 more Smart Citations
“…Propane jet freezing, introduced in the midseventies (Moor et al, 1976;Muller et al, 19801, is the inverse of spray freezing: Liquid propane cooled to near liquid nitrogen temperature is sprayed onto the sample at high velocity. Several investigators, ourselves included, have built their own version of the device (Burstein and Maurice, 1979;Linder and Staehelin, 1978;Espevik and Elgsaeter, 1981;Pscheid et al, 1981;Knoll et al, 19821, and commercial models are available from RMC, Inc., Tucson, AZ (based upon our design), and Balzers Corporation, Nashua, NH. In general, the protocol is as follows (see Figs.…”
Section: Propane Jet Freezingmentioning
confidence: 99%
“…The technique has been applied to many sample types: Aqueous suspensions and emulsions (Van Venetie et al, 1981;Costello et al, 1982;Knoll et al, 1982); tissue culture cells (Espevik and Elgsaeter, 1981;Pscheid et al, 1981;Knoll et al, 1982); suspensions of a wide variety of animal and plant cells &inder and Staehelin, 1978;Giddings and Stae-helin, 1980;Gilkey and Staehelin, 1980, and unpublished results;Ebersold et al, 1981;Knoll et al, 1982;Schmidt et al, 1983); and tissues Pollack, 1983, 1984;Swales and Lane, 1983;Hays et al, 1985;Arnn and Staehelin, unpublished results). We have found that a sandwich preparation is the best format for most sample types, because it eliminates the possibility that the sample will be damaged or blown away by the force of the propane jet.…”
Section: Propane Jet Freezingmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, current evidence, partly based on freeze-etching, suggests that tight-junctions of different types of cells differ in their lipid and protein contents (Gonzalez-Mariscal et al, 1984Stevenson and Goodenough, 1984). This may also be the reason why tight-junctions appear as continuous strands in specimens of rapidly-frozen samples in some instances, e.g., prostate glands (Kachar and Reese, 1982), monolayer cultures of Sertoli cells (Espevik and Elsgaeter, 1981b), insect perineurial cells (Swales and Lane, 1983), and as strands of particles in others, e.g., hepatocytes (Hirokawa, 198213;Nagano et al, 19821, Sertoli cells, jejunum epithelium, epididymus (Nagano et al, 19821, olfactory sensory and nonsensory ciliated epithelia (Carson et al, 1984;Meller, 1985;Menco, 1980a;Menco et al, 19841, and corneal endothelium (Raviola et al, 1980). However, the fact that Sertoli cells occur in both groups of studies (all on rat or mouse) implies that other factors, most likely the rate of freezing, also play a role.…”
Section: G Intermembranous Junctions and Othermentioning
confidence: 99%
“…Lipids: Lipid vesicles and various lipid conformations (Hauser et al, 1983;Knoll et al, 1982;Meister and Muller, 1980;Verkleij, 1985) Fusion events: Bladder, toad and frog; trichocysts, Paramecium; adrenal glands, b e vine (Hays et al, 1985;Olbricht et al, 1984;Schmidt et al, 1983) Tobacco mosaic virus Invertebrate tight-, gap, and septatejunc tions: Ventral nerue cord, cockroach, locust (Swales and Lane, 1983) Gapjunctions: Auricle, frog (Mazet et al, 1985) Mitochondria, contact points: Liver, rat (Knoll and Brdiczka, 1983;Knoll et al, 1982;Nicolay et al, 1985;Van Venetie and Verkleij, 1982) Chloroplasts: Pea and spinach (Allred and Staehelin, 1986;Cline et al, 1985;Sprague and Staehelin, 1984) Aleurone layers: Barley (Fernandez and Staehelin, 1985) Photosynthetic prokaryote: Rhodopseudomonas (Varga and Staehelin, 1983) Unicellular eukaryotic organisms: Leptomonas Staehelin, 1979,1980) Cell cultures: Various plants (Chapman and Staehelin, 1985) Cell cultures: Fibroblasts, mouse; Sertoli cells, hepatocytes, rat; monocytes, human (Epsevik and Elsgaeter, 1981b;Knoll et al, 1982;Pscheid et al, 1980) Yeast cells (Knoll et al, 1982) Algae: red algae Porphyridium cruentum; brown algae Pelvetia fastigiata; green algae Micrasterias denticulata Gilkey and Staehelin, 1986) Annulate lamellae: blastoderm, Drosophila (Stafstrom and Staehelin, 1984) Erythrocytes: Human (Espevik and Elsgaeter, 1981a) 1984a; Heuser, 1979, 1980b;Ornberg and Reese, 1981a) Tightjunctions: Epididymus, jejunum, liver, Sertoli cells, mouse; olfactory epithelium, prostate gland, rat (Hirokawa, 1982b;Kachar and Reese, 1982<...>…”
Section: Jet-freezingmentioning
confidence: 99%